EXTERNAL AND INTERNAL THREATS TO THE FINANCIAL AND ECONOMIC SECURITY OF ENTERPRISES - MARCHENKO, Valentyna; USYK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article identifies external and internal threats to the financial and economic security of enterprises in order to identify areas for ensuring the economic and financial security of enterprises in modern business conditions. The state of industrial development of the state is analyzed, which made it possible to identify negative trends that contributed to the decrease in the level of economic security of enterprises and their competitive positions. External threats and risks are identified, which include: an unfavorable macroeconomic situation in the country; instability of tax and legislative policy; high level of credit rates for business and instability of the financial and credit system; high level of competition in the market; technological changes; socio-political factors; environmental risks. Such internal threats and risks to the economic and financial security of enterprises include: low management efficiency; low labor productivity and employee motivation; internal conflicts; information leaks; depreciation of fixed assets and the use of outdated technologies and processes; financial instability and inefficient management of financial resources; imperfect inventory management; internal fraud and abuse, dishonesty on the part of employees. It is substantiated that to ensure the development of enterprises, economic and financial security should be aimed at: expanding the sources of income of the enterprise by expanding the range of products or services, as well as entering new markets; strengthening financial planning and forecasting; increasing the efficiency of risk management by implementing a risk management system; strengthening cost control; increasing the efficiency of cash flow management to ensure financial stability by ensuring the timeliness of receipts and expenditures, as well as optimizing the capital of the enterprise; ensuring financial transparency, which increases the trust of investors, creditors and partners; diversifying sources of financing; introducing modern financial technologies through new financial systems, software for data analysis; increasing financial literacy; implementing risk insurance.